Solution-processed, flexible and broadband photodetector based on CsPbBr3/PbSe quantum dot heterostructures. (30th March 2021) - Hu, Jinming; Yang, Shengyi; Zhang, Zhenheng; Li, Hailong; Perumal Veeramalai, Chandrasekar; Sulaman, Muhammad; Saleem, Muhammad Imran; Tang, Yi; Jiang, Yurong; Tang, Libin; Zou, Bingsuo
Graphical abstract: Highlights: A facile strategy for heterostructure arrays construction high-performance photodetectors is presented. Photodetectors based on CsPbBr3 /PbSe quantum dot heterostructure arrays exhibit high performance from UV to LW-IR regions. The response time of the heterostructure arrarys photodetector is shorten more than three orders of magnitude as that based on pristine PbSe. Improved both exciton dissociation and carrier transfer enhance the device performance. Abstract: Due to their promising applications in foldable displays, optical communication equipment and environmental monitoring systems, flexible and broadband optoelectronic devices have gained extensive attention in recent years. Here, a flexible and broadband photodetector based on CsPbBr3 /PbSe quantum dot (QD) heterostructures is firstly presented. The integrated QD heterostructures possess consecutive detection range from ultraviolet (UV) to long-wavelength infrared (LW-IR) regions with efficient light absorption and chemical stability, in comparison with the pristine PbSe QDs. Systematic material characterizations reveal the improved exciton dissociation, carrier transport and carrier lifetime of the QD heterostructures. Flexible photodetector Ag/CsPbBr3 /PbSe/Ag demonstrate a high responsivity of 7.17 A/W with a specific detectivity of 8.97 × 10 12 Jones under 25 μW/cm 2 365 nm illumination at 5 V. Furthermore, it could maintain 91.2 % (or 94.9 %) of its initial performance even after bending for thousands of times (or exposing in ambient air for 4 weeks). More importantly, its response time is shortened more than three orders of magnitude as that of pristine PbSe QDs-based photodetectors. Therefore, it provides a feasible and promising method for the next-generation high-performance broadband photodetectors via constructing heterostructures of various QDs.